Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s12310-016-9191-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Teacher-Reported School Climate and Depressive Symptoms in Australian Adolescents: A 5-Year Longitudinal Study

Abstract: Adolescent depression is serious and common. As adolescents spend approximately 15,000 hours in school, this setting is a logical place to seek etiological factors. Research suggests there are negative associations between school climate and adolescent depressive symptoms. However, such studies typically use student-reports of both climate and depressive symptoms; this is problematic because common method variance results when the same individual provides information on all variables, contributing to overestim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 63 publications
1
18
0
3
Order By: Relevance
“…However, the authors considered only the total score and did not report the correlations between the subscales of the SCSIM-St and depression. Similar results were found when teacher-reported school climate was assessed, that is, teacher-reported school climate was also negatively associated with students’ depression scores (Pössel et al, 2016). Salmela-Aro et al (2008) considered three subscales of school climate and regressed them on school burnout, which might also be interpreted as an indicator of the affective component of SWB.…”
Section: Introductionsupporting
confidence: 71%
“…However, the authors considered only the total score and did not report the correlations between the subscales of the SCSIM-St and depression. Similar results were found when teacher-reported school climate was assessed, that is, teacher-reported school climate was also negatively associated with students’ depression scores (Pössel et al, 2016). Salmela-Aro et al (2008) considered three subscales of school climate and regressed them on school burnout, which might also be interpreted as an indicator of the affective component of SWB.…”
Section: Introductionsupporting
confidence: 71%
“…Adolescent depressive symptoms are closely associated with maladaptive and negative developmental outcomes (Jonsson et al., ; Pössel, Rudasill, Sawyer, Spence, & Bjerg, ). For instance, studies have shown that adolescents’ depressive symptoms are associated with the risk of behavioral and emotional difficulties (e.g., Jonsson et al., ; Pössel et al., ), low self‐esteem, less effective coping, and a higher likelihood of cigarette smoking (Fletcher, ; Prinstein & La Greca, ). In addition, depressive symptoms among adolescents were associated with poorer daily adherence and greater stress severity (Baucom et al., ).…”
mentioning
confidence: 99%
“…To advance the literature, we expected that the strength of the relation between adolescents’ depressive symptoms and their academic achievement could be explained by the adolescents’ perception of the teachers’ and peers’ behaviors. Specifically, based on previous literature, indicating that adolescents who perceived their teachers as supportive, caring, and respectful of students and positive relationships with their peers also reported higher achievement and lower depressive symptoms over time (e.g., Newman et al, ; Pössel et al, ; Schwartz et al, ; Tas, ), we expected that the perception of supportive relationships with teachers and peers would be directly associated with higher academic achievement and fewer depressive symptoms. However, we could not formulate specific hypotheses about the directionality of these relations, because of the mixed findings regarding the differential roles of the teacher and peer relationships for the adolescents’ adjustment (Lynch & Cicchetti, ; Roorda et al, ).…”
Section: Depressive Symptoms and Academic Achievementmentioning
confidence: 98%
“…However, there is evidence that emotional support from teachers and depressive symptoms are not related for a sample of older adolescents (e.g., Pittard, Pössel, & Smith, ). Further, there is little evidence showing that supportive relationships with teachers are linked with adolescents’ depressive symptoms over time (e.g., Pössel et al, ; Pössel, Rudasill, Sawyer, Spence, & Bjerg, ).…”
Section: Depressive Symptoms and Academic Achievementmentioning
confidence: 99%